Southeast Asia and the Cold War - Lau, Albert, 1956- (Milton Park, Abingdon, Oxon : Routledge, 2012)
'The origins and the key defining moments of the Cold War in Southeast Asia have been widely debated. This book focuses on an area that has received less attention, the impact and legacy of the Cold War on the various countries in the region, as well as on the region itself. The book contributes to the historiography of the Cold War in Southeast Asia by examining not only how the conflict shaped the milieu in which national and regional change unfolded but also how the context influenced the course and tenor of the Cold War in the region. It goes on to look at the usefulness or limitations of using the Cold War as an interpretative framework for understanding change in Southeast Asia. Chapters discuss how the Cold War had a varied but notable impact on the countries in Southeast Asia, not only on the mainland countries belonging to what the British Foreign Office called the'upper arc', but also on those situated on its maritime'lower arc'.'--Publisher's description.
Introduction : Southeast Asia and the Cold War / Albert Lau -- Britain and the Cold War in Southeast Asia / Nicholas Tarling -- The Philippines search for security in the first years of the Cold War / Ricardo T. Jose -- Decolonization and the Cold War in Singapore, 1955-1959 / Albert Lau -- The Cold War, Malayan decolonization and the making of the Federation of Malaysia / Joseph M. Fernando -- View from the other side : early Cold War in Malaysia from the memoirs and writings of former MCP members / Danny Wong Tze Ken -- The Cold War and British Borneo : impact and legacy / Ooi Keat Gin -- The Cold War and its impact on Indonesia : domestic politics and foreign policy / Dewi Fortuna Anwar -- The Cold War and Vietnam, 1945-1960 : how did a nationalist struggle turn into a class struggle? / Pham Hong Tung -- The Vietnamese revolution in the Cold war and its impact on vietnam-asean relations during the 1960-1970s / Ly Tuong Van -- Thailand and the secret War in Laos, 1960-1974 / Sutayut Osornprasop -- The Cold War and democratization in Thailand / Kullada Kesboonchoo Mead -- The Jakarta conference on Cambodia / Ang Cheng Guan.
Includes bibliographical references and index.
Keywords: Cold War -- Political aspects -- Southeast Asia; Southeast Asia -- Foreign relations; Southeast Asia -- Politics and government -- 1945-